Yesus Juru Selamat Dalam Agama Kristen - Abudullah, Muchammdun (Tasamuh: Jurnal Studi Islam, 2017)
According to Christians, Jesus Christ is not just sent out by the local congregation. Because it emphasis on meeting with the risen Lord to accept the task personally. So, the apostles were not clergy, but the messenger of Christ to build a church. In summary, the Apostle in Ancient Greek is a term that refers to marine or naval ship goods. Later, the term also includes any person appointed as an envoy. Apostles in the Gospels refer to the twelve disciples who personally commissioned by Jesus to be the vanguard of the person who was sent as a bearer of good news. First, they start from Yarussalem and then to all the other nations in the world. Through Jesus Christ, man was called back from exile and be reconciled to God the Father in Heaven. Humans are freed from moral captivity and egoism is replaced with love and fellowship. It was Jesus Christ the only one who can free people from sin. There is no safety inside of human being rather than Him. Jesus Christ was without sin, holy and immaculate provides freedom from sin, no salvation through any other. Jesus himself said, I am the way and the truth and the life (John 14: 6). This article talks about the concept of salvationnin Christianity.